PENGUATAN KAPASITAS MASYARAKAT DALAM MENINGKATKAN IMUNITAS SELAMA PANDEMI COVID-19 - Bambang Aditya Nugraha; Sulastini; Sandra Pebrianti (LP4M STIKes Karsa Husada Garut, 2022)
Covid-19 is a disease caused by a corona virus that was first discovered in the province of Wuhan, the People's Republic of China and has become a global pandemic. The virus attacks the respiratory system and causes mild disturbances to death. The severity of the symptoms that appear is related to the state of immunity. The worse the immunity, the more susceptible to contracting Covid-19. In addition, individuals with poor immunity tend to experience severe manifestations of covid. Therefore, it is important to increase immunity during the Covid-19 pandemic. Efforts made to increase immunity include increasing community capacity through community service activities in the form of a webinar entitled